Implementasi Metode Model View Controller (MVC) Dalam Rancang Bangun Website SMK Yayasan Bakti Prabumulih - Khana Wijaya; Andi Christian (Paradigma, 2019)
Website or site may be defined as a collection of pages displaying text data, still or motion picture data, animation data, sound, video and or all of them, both static and dynamic, forming a series of interconnected buildings in which each linked to the network pages (hyperlinks). The school website has a very important role in education. SMK Bakti Prabumulih Foundation is one of the private schools that have two majors, automotive motorcycle and computer engineering and networking techniques, but this school does not have a website so many people who do not know yet remember this school is still new. In making this website the author also apply the MVC method as an option in the development of the system. The View Controller (MVC) model is a concept introduced by the inventor of Smalltalk (Trygve Reenskaug) to create one type of network data into another data type along with processing (model), isolating from the process of manipulation (controller) and view to be represented on a user interface. This application is made using the programming language Personal Hypertext Preprocessor (PHP) as a programming language and design editor Macromedia Dreamweaver, and MySQL as its database so it can help penginputan data quickly, precisely and efficiently.